Contribution to the fauna of the rove beetles (Coleoptera: Staphylinidae) of Ukraine - Gontarenko, A. V. (The Kharkiv Entomological Society Gazette, 2022)
New records of seven species of the rove beetles from Ukraine are provided, of which Pseudomedon huentheri (Hubental, 1927) is reported for the first time for Ukraine. 13 refs.